Choose Your Own Adventure: Leading Effective Case-Based Learning Sessions Using Evidence-Based Strategies - Jimmy Beck; Sahar Rooholamini; Lauren Wilson; Elena Griego; Corrie McDaniel; Rebecca Blankenburg (Association of American Medical Colleges, 2017)
Introduction Learning how to lead engaging teaching sessions is critical for faculty development and for optimizing teaching opportunities. We developed an interactive workshop to provide an evidence-based framework for designing and facilitating case-based discussions. Methods This workshop was designed as a 150‐minute large‐group session, though a 90-minute session is possible. Six to 10 students per facilitated group is optimal. Faculty training requires approximately 30 minutes prior to the session. Associated materials include guidelines to prepare faculty facilitators and participants for the large‐group discussion and small‐group practice sessions with role-plays. Also included are two prompting cases, a template for designing a large- or small-group session, a form to guide constructive feedback in the role-plays, and an evaluation form. Results This workshop was accepted for presentation at two national conferences in 2016: the Pediatric Academic Societies Meeting (PAS) and the Pediatric Hospital Medicine Conference (PHM). Average responses to "Workshop was a valuable use of my time" were 4.93 out of 5 (PAS) and 4.45 out of 5 (PHM). Average responses to "I learned information I can apply at my home institution" were 4.93 out of 5 (PAS) and 4.80 out of 5 (PHM). Discussion This large- and small-group teaching module has been incorporated into multiple pediatric residency programs and rated as highly effective by learners. Learning how to develop engaging, objective-focused group teaching sessions is an essential skill that residents, chief residents, fellows, and faculty must master to make the most of teaching opportunities.